2020
DOI: 10.1002/gea.21795
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical analysis of the truncated Viking Age trading settlement of Heimdalsjordet, Norway

Abstract: Single and multielement archaeological geochemistry has been applied to research and rescue projects for many decades to enhance our understanding of the past use of space. Often applied on one contextual plane, this ignores the complex palimpsest resulting from past occupation and soil processes. Furthermore, many important sites are now heavily truncated by plowing, leaving little more than negative features below the homogenized topsoil. These challenges require new approaches to archaeological geochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…The rarity of precious metals in soil means that detecting traces in burial environments with no naturogenic source may indicate anthropogenic activity (Wilson et al, 2008;Holliday, 2004). For example, Cannell et al (2020) observed substantial leaching of elements relating to metalworking in the later phases of Heimdalsjordet, Norway, and elemental maps of precious metals by Sylvester et al (2017) delineated around the known areas of metalworking at St. Algar's Farm, Somerset UK. However, the small size of jewellery compared to the burial environment, and low volume of trade and metal working at Boroughgate, means that detecting traces of gold and other precious metals from the soil survey was unlikely.…”
Section: Elements With Limited Interpretive Valuementioning
confidence: 99%
“…The rarity of precious metals in soil means that detecting traces in burial environments with no naturogenic source may indicate anthropogenic activity (Wilson et al, 2008;Holliday, 2004). For example, Cannell et al (2020) observed substantial leaching of elements relating to metalworking in the later phases of Heimdalsjordet, Norway, and elemental maps of precious metals by Sylvester et al (2017) delineated around the known areas of metalworking at St. Algar's Farm, Somerset UK. However, the small size of jewellery compared to the burial environment, and low volume of trade and metal working at Boroughgate, means that detecting traces of gold and other precious metals from the soil survey was unlikely.…”
Section: Elements With Limited Interpretive Valuementioning
confidence: 99%